A Model-based diagnosis method for transient and multiple faults of AOCS thrusters. Issue 17 (2016) - Pittet, C.; Falcoz, A.; Henry, D.
Abstract: This paper deals with a practical implementation for the detection and isolation of multiple transient faults of thrusters used to control the attitude of a satellite. The approach proposed in the paper only takes into account attitude control signals to detect the faults regardless of the thrusters management algorithm and modulator. Two methods are compared to compute the residuals for the detection and isolation steps: one based on a geometric analysis of faults directions, the other using observers with unknown inputs. Luenberger's observers allow the estimation of the efficiency losses providing delta-V information without orbit restitution or acceleration measurements. The algorithms are illustrated on representative closed-loop simulations with simultaneous transient losses of efficiency, and on flight telemetry where transient losses of efficiency are suspected with respect to a posteriori orbit restitution.